2009
DOI: 10.5324/nje.v18i2.29
|View full text |Cite
|
Sign up to set email alerts
|

The role of pharmacoepidemiological studies in the market withdrawal of carisoprodol (Somadril®) in Europe, 167-172

Abstract: Carisoprodol is a centrally acting muscle relaxant that has been marketed in Europe for more than 45 years. In November 2007 the European Medicines Association recommended suspension of all carisoprodol containing products in all EU countries. During recent years, several observational studies on carisoprodol have been published by our group, which works in the field of traffic medicine and pharmacoepidemiological research in general. In this paper, we review the role pharmacoepidemiological studies on carisop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Carisoprodol has a great ability to change due to its aptitude to potentiate the effects of other illegal drugs [10] . High dosage of carisoprodol led to symptoms of tolerance, dependence and withdrawal in humans [11] . Drug Enforcement Administration (DEA) [12] showed that carisoprodol abuse has expanded in the last decade in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Carisoprodol has a great ability to change due to its aptitude to potentiate the effects of other illegal drugs [10] . High dosage of carisoprodol led to symptoms of tolerance, dependence and withdrawal in humans [11] . Drug Enforcement Administration (DEA) [12] showed that carisoprodol abuse has expanded in the last decade in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Based on both these and other publications [21], a debate on the risk ⁄ benefit ratio for carisoprodol began in Norway [22]. It was concluded that the possibility of both abuse and serious intoxications made this ratio too high and that other available drugs could be considered as satisfactory alternatives.…”
mentioning
confidence: 99%
“…Carisoprodol is a centrally acting muscle relaxant, it with a high abuse potential leading to central nervous system depression and may result in symptoms that are more difficult for providers to treat (Kathy et al 2017). Moreover, carisoprodol drug is available as somadril compound which contains paracetamol 160mg, caffeine 32mg and carisoprodol 200mg (Bramness et al 2008). The drug is found in markets by a diversity names (Soma, Sodol, Somalgit, Vanadam, Sonoma, Scutamil, Carisoma, Somacid, Mio Relax, Relacton-C, Relaxibys, Rela and Soridol) as reported with Reeves et al (2012).…”
Section: Introductionmentioning
confidence: 99%